Oxford English for computing = (Tiếng Anh dành cho người sử dụng vi tính) : sách đơn ngữ - Boeckner, Keith; Brown, P. Charles; Lê Thanh ([Hà Nội] : Lao động xã hội, 2003)
Personal computing; Portable computers; Online services; Programming and languages; Computer software; ...
Keywords: English language; Technical English; English for computing; English language -- Technical English